Peningkatan Kualitas Hidup Kesehatan Masyarakat Jomblang Candisari Kota Semarang - Syurrahmi Syurrahmi; Purna Luberto; Auliya Rahma Putri; Lu’luah Feby Purwanti; Panji Satria Wiraguna (BADAN PENERBIT STIEPARI PRESS, 2023)
Health is a state of health, both physically, mentally, spiritually and socially, which enables everyone to live a productive life socially and economically. Public health is a condition that describes the level of health that occurs in society. Society is a group of individuals who live together, work together to obtain common interests and have an order of life, norms and customs that are adhered to in their environment. Public Health is a part of science that discusses and studies the prevention and treatment of disease in each individual. Some of the conditions found in the community include complaints of knee pain and back pain. The most common knee pain is osteoarthritis. Osteoarthritis is the most common form of arthritis, affecting millions of people worldwide. This disease occurs as a result of degenerative joints that affect many joint tissues. This problem arises when the protective cartilage at the ends of bones becomes damaged over time. Osteoarthritis usually occurs at the age of 40-60 years. This is caused by the process of degeneration occurring in old age. Apart from osteoarthritis, shoulder diseases are also found, such as spasms and trigger points in the upper trapezius muscle. One of the interventions or modalities provided by infrared physiotherapy. Infrared is one of the physiotherapy modalities in providing services to patients with the aim of causing a relaxation effect and reducing pain. Infrared is a peacock wave that can relieve pain and stiffness in joints and muscles. The process of vasodilation of blood vessels produced by infrared light can accelerate the removal of several pain-stimulating chemicals including bradykinin, serotonin, histamine, and proteolytic enzymes. As well as prostaglandins and substance P which increase the sensitivity of the endings of pain fibers, so that ultimately infrared can reduce the intensity of pain. Apart from providing physiotherapy intervention, they also provide socialization or counseling to the community according to the condition they are complaining about. Providing explanations regarding conditions or complaints from each community by providing education and home programs.